Mammalian Bax-induced plant cell death can be down-regulated by overexpression of Arabidopsis Bax Inhibitor-1 (AtBI-1) - Kawai-Yamada, Maki (The National Academy of Sciences, 2001)
We recently isolated the AtBI-1 (Arabidopsis Bax Inhibitor-1) gene, the expression of which suppressed Bax-induced cell death in yeast. To determine whether the same is true in the plant system, transgenic Arabidopsis plants overexpressing Bax protein under a dexamethasone (DEX)-inducible promoter were generated. On DEX treatment, such transgenic plants exhibited marked cell death at the whole-plant level, cell shrinkage, membranous destruction, and other apoptotic phenotypes. Transgenic Bax plants were retransformed with a vector containing the AtBI-1 gene (tagged with green fluorescent protein) under the control of the cauliflower mosaic virus 35S promoter. Plants expressing both Bax and AtBI-1 were able to maintain growth on DEX-treatment by sustaining intracellular integrity. Thus, we present here direct genetic evidence that the plant antiapoptotic protein AtBI-1 is biologically active in suppressing the mammalian Bax action in planta.